1339 Mineralogy and textures of asbestos: the role of single vs agglomerated fibres in toxicological experiments. (24th April 2018) - Iezzi, G; Della Ventura, G; Nazzari, Manuela; Bellatreccia, F; Di Gioacchino, M; Petrarca, C
Abstract : Introduction: Exposition to asbestos may cause adverse health effects, but a clear relationship between mineralogy and texture of fibres versus toxicity is still lacking. Toxicological studies can be properly interpreted and compared only if quantitative features of fibres are determined. Methods: Amphibole fibres were characterised by XRPD, FTIR, SEM-EDS and EMP-WDS. Fibres deposited from solutions of 0.1, 1, 10, 25, 50, 75 and 100 mg/L were counted using SEM images. The single vs agglomerated fibres was assessed. The viability of human lymphocytes exposed to the fibres was investigated by MTT test. Results: Only crystals with definite stoichiometry are present. At 0.1 and 1 mg/L the fibres are well separated, whereas between 1 and 10 mg/L they start to agglomerate. In vitro tests performed on fibres deposited at the same concentrations show that the cytotoxic effect rate decreases for asbestos concentration >10 mg/L. Conclusions: Considering that the mineralogy is constant, the decreasing rate of toxicity suggests that the hazardous potential must be attributed mainly to the single fibres, while the agglomerated fibres, whose amount increases strongly for increasing total fibres play a minor role.